PENGARUH TANJAKAN DAN VOLUME MUATAN TERHADAP PRODUKTIVITAS LORI DORONG DI HUTAN JATI - Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
An investigation on the effect of slopes and load volumes on the productivity of hand lorry was carried out at Padangan Forest District, Unit II Perum Perhutani, East Java, in 1983. In the investigation, four levels of slopes (i.e. 3, 4, 5, and 6 percent), four levels of load volumes (i.e. 3.5, 4.0, 4.5, and 5.0 m3) and the crew of 4 workers were used. The objective was to find the productivity of hand lorry opearating on several slopes and with several load volumes. The results reveal that:The productivities of log hauling by hand lorry ranged from : 7.16 to 25.09 m3km/hour with an average of 16.46 m3km/hour.Higher slope and load volume caused the decrease in lorry productivity.The relation of productivity (Y), slope (X 1) and load volume (X2) can be expressed by the following equation of linear multiple regression: Y = 48.626 - 2.199X1 - 5.342X2 with R2 = 0.58Slopes and load volumes have highly significant effect on productivities.